Situation of Implementation of Social Security Policies for Women in Dong Son District, Thanh Hoa Province, Vietnam - Oanh, Le Thi (International Journal of Humanities and Education Development (IJHED), 2023)
Social security is an important element in the development strategy of each country, a necessary condition for maintaining socio-economic stability and ensuring the building of a harmonious and civilized society. Therefore, many countries around the world, including Vietnam, have issued many policies and constantly reformed the social security system so that people can easily access and benefit from these policies. Within the framework of this article, we focus on discussing and evaluating the actual situation of implementing social security policies for women in Dong Son district, Thanh Hoa province, Vietnam, thereby giving some recommendations. possible solutions in the planning and implementation of local policies